Association of Interleukin 17F with Arthritis in Punjabi Families of Pakistan - Asia Parveen; Andleeb Batool; Maryam Mukhtar; Abdul Wajid; Naila Malkani (Journal of Bioresource Management, 2020)
Arthritis is a chronic inflammatory disease that causes severe joint pain. Interleukin 17F (IL17F) is considered as a candidate gene functionally; it mediates pro-inflammatory responses, depending on the type and site of inflammation. The present study examined the polymorphism of IL17F (rs763780 and rs2397084) among the families affected by arthritis. Demographic data and blood samples were collected from the families with at least one affected offspring with arthritis. Analysis of the IL17F gene polymorphism was performed by the digestion of DNA with NlaIII and AvaII. The results showed that IL17F rs763780 (AA, AG and GG genotypes) and rs2397084 (AA, AG and GG genotypes) were associated with arthritis (OA & RA). It was evaluated that about 65 and 21 percent of the individuals mutated with homozygous mutation for wild type allele A, heterozygous mutation A/G against selected SNPs respectively. But homozygous polymorphic allele for allele G was only found against rs2397084. Mutation in rs2397084 resulted to change Lysine into Arginine, whereas mutation in rs763780 changed Histidine into Arginine. Maternal history was found as a stronger factor in transferring arthritis. The results of this study revealed an association of arthritis with IL17F among Pakistani population.